2018
DOI: 10.1177/2309499018768100
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glenohumeral morphological factors for anterior shoulder instability and rotator cuff tear by magnetic resonance imaging

Abstract: Objective: The aim of this study was to investigate whether there are glenohumeral morphological differences between normal population, glenohumeral instability, and rotator cuff pathology. Method: In this study, shoulder magnetic resonance (MR) images of 150 patients were evaluated. Patients included in the study were studied in three groups of 50 individuals: patients with anterior shoulder instability in group 1, patients with rotator cuff tear in group 2, and control subjects without shoulder pathology in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
1
Order By: Relevance
“…According to an MRI study, the humeral head is larger in both the transverse and longitudinal axes in the AnI group, but smaller both transversely and longitudinally in the rotator cuff group 8 and is consistent with a CT study that showed that the humerus is larger in both the vertical and horizontal planes in the AnI group. 11 We believe that AI was smaller in the AnI group because the humeral head was larger, and AI was larger in the RCT group because the humeral head was smaller than that in the control group.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…According to an MRI study, the humeral head is larger in both the transverse and longitudinal axes in the AnI group, but smaller both transversely and longitudinally in the rotator cuff group 8 and is consistent with a CT study that showed that the humerus is larger in both the vertical and horizontal planes in the AnI group. 11 We believe that AI was smaller in the AnI group because the humeral head was larger, and AI was larger in the RCT group because the humeral head was smaller than that in the control group.…”
Section: Discussionsupporting
confidence: 84%
“…Anterior Shoulder Instability (AnI) and RCT are related to changes in the glenohumeral morphology, such as Glenoid Version (GV), GI, and humeral head diameter. 7 , 8 GI is a part of CSA and AI, and the humeral head diameter is a part of AI. As studies have shown, GI and GV in patients with RCT or AnI are different from those in normal population 9 , 10 and the humeral head is smaller in RCTs and larger in AnI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humerus retroversiyonu glenohumeral eklem mekaniğini etkiler. Omuz ekleminin mobilite ve stabilitesi retroversiyon miktarına bağlıdır (10)(11)(12)(13)(14) . Bu çalışmanın amacı, diafiz kırığı sonrası iyileşmiş humerus ile aynı bireyin karşı taraf sağlam humerus versiyon açılarının BT ile değerlendirilmesi ve versiyondaki değişimin fonksiyonel sonuçlara olan etkisinin incelenme-sidir.…”
Section: Discussionunclassified
“…The aforementioned parameters were chosen because they are either considered risk factors for RCT development or used by orthopedic surgeons for surgical planning. 4,6,8,11,18,23,25,27,30,35,39,40,44 In addition, 5 MRI parameters were included in the model for the same reasons:…”
Section: Regression Modelmentioning
confidence: 99%